Tourism Villages for Micro and Small Enterprises Labor Absorption - Sugiharti, Rr Retno; Panjawa, Jihad Lukis; Pamela, Queen; Kurniawan, Muhammad Arif; Guritno, Danur Condro (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2023)
Micro, Small, and Medium Enterprises (MSMEs) are the most important pillars of Indonesia’s economy. It has considerable contribution in providing employment in the informal sector. However, the high absorption of labor accompanied by the increased number in MSMEs in Indonesia cannot be separated from the existing challenges. This study aims to analyze the determinants of employment in the Micro and Small Enterprises sector (MSEs). MSEs actors in the tourism village area, Patuk sub-district, Gunungkidul, Yogyakarta. This research is focused on the role of the type of business and the status of the tourism village. The analytical tool used is the robust ordinary Least Square (OLS) method. The results showed that turnover and length of business had a real impact on increasing the absorption of MSEs workers according to the type of business and the status of the tourism village. Other findings show that Micro and Small handicraft businesses showed the highest employment absorption in tourism village with developed status, followed by businesses in the service, processed food, and trade sectors. The same results are also shown in the status of developing tourist villages. The potential of tourist villages with the advantages of the business sector has a real impact on increasing employment. Therefore, policymakers need to formulate strategies for the development of tourist villages to improve the welfare of local communities.